Initiative for Climate Action Transparency (ICAT) for adaptation in Kenya - Kinyua, Ivy Wambui; Mwongera, Caroline; Ndetu, Veronica (2022)
The Initiative for Climate Action Transparency (ICAT) is an unincorporated multi-stakeholder partnership, which aims to increase helps countries better assess the impacts of their climate policies and actions, and fulfil their transparency commitments. In Kenya, the Alliance of Bioversity International and International Center for Tropical Agriculture (CIAT) are implementing the project in partnership with the Ministry of Agriculture, Livestock, Fisheries, and Cooperatives, working closely with the UNEP Copenhagen Climate Centre. This is a factsheet about ICAT's focus areas, results, and next steps in Kenya.